Yon’s letter, by Julio Vila - Sanz Barajas, Jorge (Razón y fe, 2018)
The fight for identity, the bet on of what is unique and exclusive, in addition to isolating, it also dries and kills. It even dries and kills community life, trust and love. The struggle exclusively for identity, makes the protagonist of Yon’s letter, Andoitz, end up internally fractured, unable to freely express his emotions, paralyzed by fear and led, finally, to an announced death.